"I Want to Help Others Like Me": A Pilot Qualitative Study on Patients' Participation in a Screening for Distress Program. (June 2022) - Rivest, Jacynthe; Desbeaumes Jodoin, Véronique; Martineau, Joé T; Folch, Nathalie; Charpentier, Danielle
Screening for distress was implemented in our academic hospital with the engagement of patients as partners. Little is known about how they appreciate such participation. This pilot qualitative study aimed to explore their experience. Six participants completed a semi-structured interview, which was transcribed verbatim. Thematic analysis was performed on the transcripts. Four themes emerged: "opinions about their participation", "working with others", "role of patient partners", and "barriers encountered". Mean global satisfaction reported on a Likert scale reached 8.92 over 10. Our preliminary findings suggest that patients-as-partners appreciated their participation, and also identified barriers that should be explored in future quality improvement (QI) projects.